PERANCANGAN IT GOVERNANCE LAYANAN AKADEMIK MENGGUNAKAN FRAMEWORK INFORMATION TECHNOLOGY INFRASTRUCTURE LIBRARY (ITIL) VERSI 3 (STUDI KASUS: UIN SGD BANDUNG) - Ichsan Taufik (JURNAL ISTEK, 2011)
The main activity in higher education in accordance with its main function is as education is academic service providers. This paper conducted a study of how the governance of information technology related to academic service to the organization UIN SGD Bandung, so that using information technology especially in terms of academic service which is a new service can help the organization in achieving its objectives. This paper refers to one of the governance framework for information technology that is ITIL (IT Infrastructure Library) version 3 which is the latest version of the ITIL framework is based on lifecycle. One of the cycles that exist in ITIL version 3 is the IT Service Operation which is the focus area of this paper. The procedure in this paper are: 1. Study of literature from a variety of relevant literature. 2. The collection of data and information through survey, observation, interview and collecting documents. 3. Data analysis. 4. Creating strategies and evaluate the application of IT Service Operation in UIN SGD Bandung. From the survey which was conducted with students, lecturers and employees of IT and Non IT regarding their response to conditions of readiness for implementing IT Service Operation in UIN SGD Bandung, so we found the conditions currently in the initial and repeatable stage where the condition is still necessary corrective steps which related to the implementation IT Service Operation. In this paper conducted an evaluation of strategy formulation and implementation of improvements to IT Service Operation in UIN SGD Bandung using frameworks IT Infrastructure Library (ITIL) version 3.